Peningkatan Kemampuan Membaca Permulaan Melalui Metode Drill - Rusmiy Sumanty (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The purpose of writing best practice is to describe the application of drill methods and Kacamata strategies (beautiful cards of various letters, syllables, and words) in improving the ability to read the1 grade students of elementary school 3 Damar, identify constraints of Drill. Problem-solving strategies used are the drill method and the